Metal-organic frameworks as potential catalysts for biodiesel production and biomass conversion: Mechanism and characteristics - Le, Thanh Tuan; Sharma, Prabhakar; Le, Huu Son; Le, Huu Cuong; Le, Duc Trong Nguyen; Cao, Dao Nam; Truong, Thanh Hai; Tran, Viet Dung (Industrial crops and products, 2024)
This comprehensive assessment examines the key challenges confronting the transportation sector, a major source of greenhouse gas emissions. These issues include rising fuel costs and declining reserves. Although electric mobility is becoming more popular in light-duty transportation, heavy-duty trucks continue to rely heavily on diesel engines. Biofuels are the subject of extensive research as both a financially viable and environmentally conscious alternative. Biodiesel derived from animal fats and vegetable oils is widely recognized for its natural decomposition, low toxicity, low pollutant emissions, and renewable properties. Catalysts aid in the chemical transformation of biomass, an important renewable energy source around the world. Solid acid catalysts are becoming increasingly important in improving the quality of biomass. This study analyzes the ability of metal-organic frameworks (MOFs), which are hybrid nanoporous materials, to act as catalysts in biomass conversion and biodiesel production. MOFs offer exceptional performance attributes, including large surface areas and customizable pore architectures, making them highly versatile for various applications. The review analyzes the role of MOF-based catalysts in accelerating biomass conversions and biodiesel synthesis, focusing on their structural properties, benefits, and challenges. This work provides useful insights into the significance of MOFs. It emphasizes MOFs as critical catalysts for promoting green chemistry practices and advancing the paradigm of sustainable energy production. •MOF is found as efficient catalyst for biodiesel production and biomass conversion.•Synthesis process and main properties of MOF catalysts are completely presented.•Catalytic reaction mechanisms of MOF for biofuel synthesis are scrutinized.•Challenges and perspectives of MOF catalysts are discussed in detail.